Improving mathematical problem-solving abilities through the development of Articulate Storyline learning media - Netriwati Netriwati; Ainaya Mourina Ulfa; Novian Riskiana Dewi (Universitas Sarjanawiyata Tamansiswa, 2025)
Students' mathematical problem-solving abilities are still relatively low, thus requiring innovative, effective, and contextual learning media. This study aims to develop learning media based on Articulate Storyline to improve junior high school students’ mathematical problem-solving skills by integrating Polya’s problem-solving steps. The research method employed is Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The research instruments included expert validation questionnaires, student response questionnaires, and mathematical problem-solving ability tests. The results showed that the developed media was valid according to media experts (score: 3.39) and material experts (score: 3.27), and was considered highly attractive by students (average score: 3.62 for the small group and 3.49 for the large group). The effectiveness test using N-gain indicated an improvement in students’ mathematical problem-solving skills, with average scores of 0.67 (small group) and 0.69 (large group), both falling into the moderate category. These findings imply that learning media based on Articulate Storyline is effective and feasible to be used as an alternative interactive learning tool for enhancing students’ mathematical problem-solving skills. This research contributes theoretically to the development of media based on Polya’s indicators and practically by providing a media model that can be adapted by mathematics teachers.